Navigating the Complement Pathway to Optimize PNH Treatment with Pegcetacoplan and Other Currently Approved Complement Inhibitors - Hillmen, Peter; Horneff, Regina; Yeh, Michael; Kolev, Martin; Deschatelets, Pascal (International journal of molecular sciences, 2024)
Paroxysmal nocturnal hemoglobinuria (PNH) is a rare and potentially life-threatening hematologic disorder caused by a somatic mutation in a relevant portion of hematopoietic stem cells. Mutation of the phosphatidylinositol glycan biosynthesis class A (PIGA) gene prevents the expression of cell-surface proteins, including the complement regulatory proteins CD55 and CD59. With decreased or a lack of CD55 and CD59 expression on their membranes, PNH red blood cells become susceptible to complement-mediated hemolysis (symptoms of which include anemia, dysphagia, abdominal pain, and fatigue), leading to thrombosis. State-of-the-art PNH treatments act by inhibiting the dysregulated complement at distinct points in the activation pathway: late at the C5 level (C5 inhibitors, eculizumab, ravulizumab, and crovalimab), centrally at the C3 level (C3/C3b inhibitors and pegcetacoplan), and early at the initiation and amplification of the alternative pathway (factor B inhibitor, iptacopan; factor D inhibitor, danicopan). Through their differing mechanisms of action, these treatments elicit varying profiles of disease control and offer valuable insights into the molecular underpinnings of PNH. This narrative review provides an overview of the mechanisms of action of the six complement inhibitors currently approved for PNH, with a focus on the C3/C3b-targeted therapy, pegcetacoplan.